Time‐Resolved Measurements of Plasma Properties Using Electrostatic Probes in the Cross‐Field Discharge of a Hall Effect Thruster. Issue 1 (9th January 2013) - Dannenmayer, K.; Kudrna, P.; Tichý, M.; Mazouffre, S.
Abstract Time‐resolved measurements of the plasma parameters are performed in the plume of a cross‐field discharge. The plasma potential is measured with a cylindrical Langmuir probe and an emissive probe. The electron temperature and density are measured with a cylindrical Langmuir probe. The cross‐field discharge is maintained in a harmonic oscillation regime to guarantee reproducible conditions for all measurements (© 2013 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)